2005
DOI: 10.1021/jp045594x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mesoporous Carbons Using Ordered and Disordered Mesoporous Silica Templates and Polyacrylonitrile as Carbon Precursor

Abstract: Mesoporous carbons were synthesized from polyacrylonitrile (PAN) using ordered and disordered mesoporous silica templates and were characterized using transmission electron microscopy (TEM), powder X-ray diffraction, nitrogen adsorption, and thermogravimetry. The pores of the silica templates were infiltrated with carbon precursor (PAN) via polymerization of acrylonitrile from initiation sites chemically bonded to the silica surface. This polymerization method is expected to allow for a uniform filling of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
168
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(177 citation statements)
references
References 113 publications
8
168
1
Order By: Relevance
“…The EISA method made it feasible to regulate pore structures and pore sizes and allowed the preparation of various mesoporous materials from water-insoluble systems, including mesoporous silicas [2,7,8,10,[15][16][17][18], mesoporous resins [3,6,9,11], mesoporous TiO 2 [19][20][21], and mesoporous carbons [2,4,12,16,[22][23][24]. The typical procedure used to prepare ordered mesoporous carbons, so-called "template synthesis" [25][26][27][28][29][30], involves the use of mesoporous silicas as hard templates, impregnation of carbon precursors into their mesochannels, carbonization under an inert gas, and finally dissolving the hard template of the "ordered mesoporous silica" through etching in HF (aq) . Although such template syntheses have been used broadly, they can be ineffective means of fabrication of mesoporous carbons because of the many steps required and complicated processing.…”
Section: Introductionmentioning
confidence: 99%
“…The EISA method made it feasible to regulate pore structures and pore sizes and allowed the preparation of various mesoporous materials from water-insoluble systems, including mesoporous silicas [2,7,8,10,[15][16][17][18], mesoporous resins [3,6,9,11], mesoporous TiO 2 [19][20][21], and mesoporous carbons [2,4,12,16,[22][23][24]. The typical procedure used to prepare ordered mesoporous carbons, so-called "template synthesis" [25][26][27][28][29][30], involves the use of mesoporous silicas as hard templates, impregnation of carbon precursors into their mesochannels, carbonization under an inert gas, and finally dissolving the hard template of the "ordered mesoporous silica" through etching in HF (aq) . Although such template syntheses have been used broadly, they can be ineffective means of fabrication of mesoporous carbons because of the many steps required and complicated processing.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve graphitization of ordered mesoporous carbon frameworks, four methods are considered feasible: 1) Choosing an appropriate, easily graphtiized carbon source, such as mesophase pitch, [ 7 , 8 ] polyaromatic hydrocarbons, [ 9 , 10 ] aromatic molecules, [ 10 ] aniline, [ 11 ] or acrylonitrile. [12][13][14] As an example, Ryoo and co-workers [ 9 ] fi rst reported fabrication of nanocast mesoporous graphitic carbons by fi lling Al-containing mesoporous silica (Al-SBA-15) mesochannels with acenaphthene, converting the acenaphthene in situ to mesophase pitch, and then graphitizing it in a special alloy autoclave at 900 ° C and under vacuum. 2) High-temperature ( > 900 ° C) chemical vapor deposition (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Kruk et al prepared mesoporous carbons with sharp distribution pore size from PAN by using ordered and disordered mesoporous silica templates, and the detailed characteristics were investigated. 16 Ryoo also studied the similar structures prepared by using sucrose.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Kruk et al prepared mesoporous carbons with sharp distribution pore size from PAN by using ordered and disordered mesoporous silica templates, and the detailed characteristics were investigated. 16 Ryoo also studied the similar structures prepared by using sucrose.17 Giunta et al prepared carbon-silica nanocomposites from the pyrolysis of PAN.18 The carbonization has been carried out for electro-spun thin PAN fibers to pursue smooth thermal stabilization and carbonization as well as to avoid the occurrence of defects and voids within the fibers by chemical reactions under the thermal stabilization and carbonization. [19][20][21][22] Recent studies reported that the composite of PAN and multi-wall carbon nanotubes (MWNTs) were prepared by gelation/crystallization from PAN solution containing MWNTs.…”
mentioning
confidence: 99%